Differentiation stage-specific expression of transcriptional regulators for epithelial mesenchymal transition in dentate granule progenitors - Ohyama, Kyoji; Shinohara, Hiroshi M.; Takayama, Natsumi; Ogawa, Rina; Omura, Shoichiro; Hayashida, Mio; Takahashi, Tokiharu (Frontiers in Neuroscience, 2024)
During the development of the mouse dentate gyrus (DG), granule neuronal progenitors (GNPs) arise from glial fibrillary acidic protein (GFAP)-expressing neural stem cells in the dentate notch. However, the transcriptional regulators that control their stepwise differentiation remain poorly defined. Since neurogenesis involves epithelial-tomesenchymal transition (EMT)-like processes, we investigated the spatio-temporal expression profiles of the EMT transcription factors Zeb1, Scratch2 (Scrt2) and Nkx6-2 in relation to known GNP markers. Our results show that Zeb1 and Scrt2 exhibit sequential, but partially overlapping expression across embryonic and postnatal stages of GNP differentiation. Zeb1 is highly enriched in gfap-GFP+/Sox2+ neural stem/progenitor pools and subsets of Tbr2+/Prox1+/NeuroD+ intermediate GNPs, whereas Scrt2 predominates in Tbr2+/Prox1+/NeuroD+ GNPs. Strikingly, the neuronal EMT regulator Nkx6-2 shows selective expression in postnatal Tbr2+/Prox1+ GNPs, but it is excluded from embryonic counterparts. This temporally coordinated yet distinct expression of Zeb1, Scrt2 and Nkx6-2 reveals discrete transcriptional programmes orchestrating GNP differentiation and neurogenic progression at embryonic versus postnatal stages of DG neurogenesis.